Reticence among English department students in an online speaking class: Contributing factors and remedies - Adiatma, Putri Sanda; Subekti, Adaninggar Septi (Journal of English Language Teaching and Learning (JETLE), 2025)
This study seeks to investigate second/foreign language (L2) reticence among students taking an online public speaking class at an English Language Education Department in Java, Indonesia. These participants were selected because based on a preceding observational study, L2 reticence was present among these target participants in the observed public speaking class. More specifically, the present study intends to discover the possible causes of L2 reticence and the possible strategies to alleviate it. To achieve this goal, four reticent students, identified based on the observation data from the preceding study, as well as two teachers who taught the class, were individually interviewed. The interview data were analysed using Thematic Analysis. The results suggested the student participants' beliefs that low confidence levels and fear of possible embarrassment were major causes of L2 reticence. The teacher participants, furthermore, believed that constantly monitored group discussions and teacher psychological support could lessen students' L2 reticence. Implications include setting clear expectations and assigning roles to each student to keep students accountable. Teachers should also maintain a democratic classroom environment where students can feel more at ease in expressing their thoughts.